Next-generation whole-exome sequencing contribution to identification of rare autosomal recessive diseases - Rančelis, Tautvydas; Cimbalistienė, Loreta; Kučinskas, Vaidutis (Acta medica Lituanica, 2013)
A rare disease is any disease that affects a small percentage of the population. In the European Union a disease is defined as rare if it affects less than 1 in 2,000 people. Despite a small percentage of affected people by one disease, the total number of rare diseases is estimated to be around 7,000–8,000, thus, because of their large number they have an impact on many people and even 30 million of European Union citizens may be suffering from them. Research of rare diseases may help to explain their mechanism or to develop more advanced diagnostics. Classical strategies for studies of rare autosomal recessive diseases encounter with additional problems (multiple genetic variants, de novo mutations, extremely rare cases) that make these strategies not enough effective. Next generation whole-exome sequencing (WES) opened a new page in Mendelian disease gene discovery – enabling to study autosomal recessive diseases in a new way. During 3 years of WES usage many novel mutations of autosomal recessive disease genes were discovered.